Dampak Perlambatan Ekonomi Nasional terhadap Kepatuhan Pebayaran Iuran Peserta BPJS Kesehatan - Karmila; Abustan Nur; Afdinda Rahmi; Nuril Fauzah (CENDEKIA : Jurnal Penelitian dan Pengkajian Ilmiah, 2026)
The slowdown of the national economic condition is one of the factors affecting the sustainability of the National Health Insurance (JKN) program, particularly regarding the compliance of independent participants in paying BPJS Health contributions. Economic instability, characterized by declining income, increasing cost of living, and household financial pressure, can impact participants’ ability and willingness to meet contribution obligations regularly. This study aims to examine the effect of economic slowdown on the compliance of BPJS Health contributions among independent participants using a literature review approach. The method employed is a literature review by analyzing various national scientific articles published within the last five years (2020–2024) and obtained from accredited journals and online scientific repositories. The findings indicate that economic aspects, such as income level, ability to pay, and willingness to pay, play a significant role in the level of contribution compliance. In addition to economic factors, participants’ understanding of JKN benefits, perception of healthcare service quality, as well as contribution policies and the implementation of sanctions also influence compliance. Economic slowdown tends to reduce contribution compliance, especially among low-income participants and informal sector workers. Therefore, strategic efforts by the government and BPJS Health are necessary through more adaptive policies, targeted subsidies, enhanced participant education, and the development of flexible contribution schemes to maintain the sustainability of the JKN program amid national economic dynamics.